Reimagining Zen in a Secular Age: Charles Taylor and Zen Buddhism in the West, by André van der Braak - Kooijmans, Leon (Interreligious studies and intercultural theology, 2022)
Reimagining Zen in a Secular Age: Charles Taylor and Zen Buddhism in the West, by André van der Braak, Brill | Rodopi, 2020. xii + 260 pp., Pb. €55. ISBN 978-9004435070